INTEGRAL YUGOSLAVISM AND THE POLITICS OF SERBIAN LANGUAGE TEACHING IN INTERWAR YUGOSLAVIA (1918-1941) (Heritage, 2026)
This paper examines the influence of the ideology of integral Yugoslavism on the teaching of Serbian, or the so-called “national language”, in the schools of interwar Yugoslavia (1918-1941). The study is based on an analysis of curricula, syllabi, and textbooks. Its aim is to demonstrate that language instruction served as a tool of cultural unification, political socialization, and the cultivation of loyalty to the state. The analysis of normative documents, readers, and teaching manuals shows that schooling in the interwar period fulfilled both educational and ideological functions. This is particularly evident in the promotion of the idea of a “single national language,” a shared literary tradition, and models of desirable national identity. Through content analysis, the paper connects the historical reconstruction of school policy with sociolinguistic and pedagogical insights and shows how language teaching contributed to the construction of national unity. Situated within the broader context of European language policy and state-building pedagogy, the paper portrays education as a sphere in which the cultural, ideological, and political strategies of modern states intersect.
Keywords: Serbian language teaching; language ideology; integral Yugoslavism; educational policy; textbook analysis; interwar Yugoslavia.